Perioperative Considerations for Tracheostomies in the Era of COVID-19. (August 2020) - Gosling, Andre F.; Bose, Somnath; Gomez, Ernest; Parikh, Mihir; Cook, Charles; Sarge, Todd; Shaefi, Shahzad; Leibowitz, Akiva
Abstract : The morbidity, mortality, and blistering pace of transmission of infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to an unprecedented worldwide health crisis. Coronavirus disease 2019 (COVID-19), the disease produced by SARS-CoV-2 infection, is remarkable for persistent, severe respiratory failure requiring mechanical ventilation that places considerable strain on critical care resources. Because recovery from COVID-19–associated respiratory failure can be prolonged, tracheostomy may facilitate patient management and optimize the use of mechanical ventilators. Several important considerations apply to plan tracheostomies for COVID-19–infected patients. After performing a literature review of tracheostomies during the severe acute respiratory syndrome (SARS) and Middle East Respiratory Syndrome (MERS) outbreaks, we synthesized important learning points from these experiences and suggested an approach for perioperative teams involved in these procedures during the COVID-19 pandemic. Multidisciplinary teams should be involved in decisions regarding timing and appropriateness of the procedure. As the theoretical risk of disease transmission is increased during aerosol-generating procedures (AGPs), stringent infectious precautions are warranted. Personal protective equipment (PPE) should be available and worn by all personnel present during tracheostomy. The number of people in the room should be limited to those absolutely necessary. Using the most experienced available operators will minimize the total time that staff is exposed to an infectious aerosolized environment. An approach that secures the airway in the safest and quickest manner will minimize the time any part of the airway is open to the environment. Deep neuromuscular blockade (train-of-four ratio = 0) will facilitate surgical exposure and prevent aerosolization due to patient movement or coughing. For percutaneous tracheostomies, the bronchoscopist should be able to reintubate if needed. Closed-loop communication must occur at all times among members of the team. If possible, after tracheostomy is performed, waiting until the patient is virus-free before changing the cannula or downsizing may reduce the chances of health care worker infection. Tracheostomies in COVID-19 patients present themselves as extremely high risk for all members of the procedural team. To mitigate risk, systematic meticulous planning of each procedural step is warranted along with strict adherence to local/institutional protocols.